2015
DOI: 10.1038/jcbfm.2015.99
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Histone Methyltransferases SUV39H1 and G9a Leads to Neuroprotection in an in vitro Model of Cerebral Ischemia

Abstract: Cerebral ischemia induces a complex transcriptional response with global changes in gene expression. It is essentially regulated by transcription factors as well as epigenetic players. While it is well known that the inhibition of transcriptionally repressive histone deacetylases leads to neuroprotection, the role of histone methyltransferases in the postischemic transcriptional response remains elusive. We investigated the effects of inhibition of the repressive H3K9 histone methyltransferases SUV39H1 and G9a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…It remains ambiguous whether the effects of chaetocin are entirely mediated through SUV39H and the specificity of chaetocin has been called into question20. Similar to our study, Schweizer et al 21. have reported that chaetocin administration is associated with neuroprotection in an in vitro model of cerebral ischaemia.…”
Section: Discussionsupporting
confidence: 70%
“…It remains ambiguous whether the effects of chaetocin are entirely mediated through SUV39H and the specificity of chaetocin has been called into question20. Similar to our study, Schweizer et al 21. have reported that chaetocin administration is associated with neuroprotection in an in vitro model of cerebral ischaemia.…”
Section: Discussionsupporting
confidence: 70%
“…Its role is complex and may differentially affect gene expression, depending on temporal and spatial changes on the tissue level. Studies of animal and in vitro models of stroke demonstrated that histone methylation is affecting stroke severity during aging [ 55 ] and neuronal resistance in a model of hypoxic metabolic stress [ 56 ]. Besides that, studies implicated the connection of histone methylation with proinflammatory cytokines [ 57 ].…”
Section: Epigenetic Regulation Of Immune Response In Strokementioning
confidence: 99%
“…Aberrant regulation of those MAPKs is also related to numerous pathological conditions, as well as cancer.Recent studies have shown that arginine and lysine methylation also regulate the activities of MAPKs [73]- [75] . In invitro study of rat model, effects of inhibition of the repressing H3K9 histone methyltransferases SUV39H1 and G9a (responsible for H3K9 methylation) on neuronal survival and shelter in O 2 glucose deprivation atmosphere (OGD), BDNF gene expression was upregulated around promoter I, II and III selected in cerebral ishchemia [76] . Hypoxic environment in cancer cells are related with the initiation of methyl transferase G9a activity inhibiting demethylation.…”
Section: Histone Methylationmentioning
confidence: 99%